Salivary total protein and electrolyte profile comparison in HIV patients - Pratiksha Mahajan; Supriya Kheur (Elsevier, 2021)
Aim or Purpose: Present study aims to assess potential difference in salivary total protein and electrolyte levels in HIV patients with and without ART. Materials and Methods: Patients were divided into 3 groups Group A (HIV-1 positive patient under ART for at least 6 months) 66, Group B (HIV-1 positive patient not on ART) 66, Group C (HIV negative patients)66. Resting whole saliva of patients was collected by passive drooling into sterile glass tube by Colin Dawe's method. 2 ml of collected saliva sample was then analysed for total protein evaluation by Biuret method. Electrolytes in the samples were analysed by an ion-selective electrode technique. After evaluation, data were entered in Excel, analysed by SPSS version 20. Quantitative data were summarised using mean and standard deviation (SD). Statistical tests used to analyze the data included one-way ANOVA with post hoc Tukey test. Results: There was statistically significant difference in salivary protein (p = 0.000) and electrolyte (Sodium, p = 0.000; Potassium, p = 0.039; chlorine, p = 0.027; ionized calcium, p = 0.002) levels among three groups. Conclusions: HIV positive individuals with and without ART have alteration in salivary composition. Some of these alterations (total protein and iCa levels) are due to HIV infection, while others (Na, K, Cl) could be due to ART or a combined effect of both. Salivary changes in HIV positive individuals could predispose them to oral diseases. Thus, regular oral examination and prophylactic regimen must be formulated to maintain their oral hygiene and quality of life.